(3HOjYjGf aj eOM GdfHi Udi Gddg Ydjg hSdes - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3jGMSf eWdY ef Cghi HPi Sde HQGYI GdThb ai ESJgdGdgG Cdei s
(3BNQgG (B:s
(3gPG eOjMi aEf fdJ GdbHhd Hg SYOJ ChdG aMSHi ehba GdHge s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs